2010
DOI: 10.1073/pnas.1008603107
|View full text |Cite
|
Sign up to set email alerts
|

CO impedes superfast O 2 binding in ba 3 cytochrome oxidase from Thermus thermophilus

Abstract: Kinetic studies of heme-copper terminal oxidases using the CO flow-flash method are potentially compromised by the fate of the photodissociated CO. In this time-resolved optical absorption study, we compared the kinetics of dioxygen reduction by ba 3 cytochrome c oxidase from Thermus thermophilus in the absence and presence of CO using a photolabile O 2 -carrier. A novel doublelaser excitation is introduced in which dioxygen is generated by photolyzing the O 2 -carrier with a 355 nm laser pulse and the fully r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
102
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(111 citation statements)
references
References 32 publications
8
102
1
Order By: Relevance
“…The maximum turnover of the oxygen reductases is typically in the range of 100-1;000 electrons∕s. If the second order rate constant for the initial reaction of O 2 with the enzyme is 10 8 M −1 s −1 [the value measured for the A-family (36)], then at 10 −9 M O 2 the formation of the initial complex between the enzyme and oxygen will be rate limiting at about 10 −1 s −1 . Even though the O 2 concentration within the hydrophobic lipid membrane is higher than in water, the rate of respiration might be too slow to maintain the necessary membrane potential.…”
Section: Adaptation Of Aerobic Respiration To Low Oxygen Environmentsmentioning
confidence: 99%
“…The maximum turnover of the oxygen reductases is typically in the range of 100-1;000 electrons∕s. If the second order rate constant for the initial reaction of O 2 with the enzyme is 10 8 M −1 s −1 [the value measured for the A-family (36)], then at 10 −9 M O 2 the formation of the initial complex between the enzyme and oxygen will be rate limiting at about 10 −1 s −1 . Even though the O 2 concentration within the hydrophobic lipid membrane is higher than in water, the rate of respiration might be too slow to maintain the necessary membrane potential.…”
Section: Adaptation Of Aerobic Respiration To Low Oxygen Environmentsmentioning
confidence: 99%
“…This raises important issues as to the means by which the electron transfer to these transient species is regulated for conformational transitions that are required for any pumping mechanism to occur (6,7,9,10). In the oxidase/peroxide reaction at high pH, it has been demonstrated that the addition of stoichiometric amounts of H 2 O 2 to oxidized enzyme leads to the formation of the 607 nm form having the proposed Fe(IV)ϭO .…”
mentioning
confidence: 99%
“…Electron Transfer in Cytochrome c Oxidase-Cytochrome c oxidase utilizes a complex pattern of ET through strongly coupled substrate and redox-dependent sites that involve intermediate cofactors and nonadiabatic, long distance, single-electron tunneling between weakly coupled redox centers (5,11,45,46,66). In the aerobic electron transfer chain of T. thermophilus, electrons are donated by cytochrome c 552 and enter ba 3 -cytochrome c oxidase through the dinuclear Cu A site (39,58,59,67). The interactions between this pair were found to be mainly hydrophobic (68), in contrast to other oxidases where an electrostatic character was described.…”
mentioning
confidence: 99%